Gene co-expression network and differential expression analyses reveal key genes for weaning weight in Simmental-Holstein crossbred cattle - Saina Yan; Fen Pei; Jingfnag Si; Md. Yousuf Ali Khan; Sihai Ou; Yang Yang; Zongsheng Zhao; Alfredo Pauciullo; Yi Zhang (Animal Biotechnology)
Weaning weight is a key indicator of the early growth performance of cattle. An understanding of the genetic mechanisms underlying weaning weight will help increase the accuracy of selection of breeding animals. In order to identify candidate genes associated with weaning weight in Simmental-Holstein crossbred cattle, this study generated RNA-Sequencing (RNA-seq) data from 86 crossbred calves (37 males and 49 famales) and measured their weaning weight and body size traits (wither height, body length, chest girth, rump width, and rump length). Differential gene expression analysis and weighted gene co-expression network analysis (WGCNA) were performed. A total of 498 differentially expressed genes (DEGs) were identified between the low weaning weight (LWW) group and the high weaning weight (HWW) group. Weaning weight was transcriptionally correlated (FDR < 0.05) with four of the eleven co-expression gene modules. By intersecting DEGs and hub genes of the four modules, we identified a final set of 37 candidate genes enriched in growth, development, or immune-related processes. In addition, one co-expression module was significantly correlated with all the five body size traits (P < 0.05), from which MX1 was identified as a key candidate gene through protein-protein interaction (PPI) analysis of hub genes. Further evidence from cattle transcriptome-wide association study analysis (TWAS) and human phenome-wide association study (PheWAS) validated significant associations of CACNA1S, SEMA7A, VCAN, CD101, CD19, and CSF2RB with growth and development traits (P < 0.05). Notably, CACNA1S and CD19 were also associated with typical immune traits such as B cell proliferation, differentiation, and activation. In conclusion, this study reveals new candidate genes significantly associated with weaning weight in Simmental-Holstein crossbred cattle, providing a basis for further exploration of the genetic mechanisms behind growth traits of cattle.